(untitled) (Research, Society and Development, 2022)
Atopic dermatitis (AD), also known as atopic eczema, is a persistent and relapsing inflammatory disease of the pores and skin that evolves with intervals of activation. The study aims to demonstrate approaches in the treatment of atopic dermatitis. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Nursing Database (BDENF) and Medical Literature Analysis. and Retrieval System Online (MEDLINE), using the following Health Science Descriptors (DeCS): “Atopic Dermatitis” and “Therapeutics”. Combined with each other by the boolean AND operator. As inclusion criteria: articles available online, in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. Eight categories of treatments emerged to be studied. Given the above, we can see that there is a range of treatments for atopic dermatitis, being selected according to severity, level of response and medical and/or family history.